2009
DOI: 10.1111/j.1439-0388.2008.00772.x
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of genetic variability in the Czech Dachshund population using microsatellite markers

Abstract: The primary goal of this study was to analyse genetic variation within and among six Dachshund varieties in the Czech Republic using 10 microsatellites from StockMarks Paternity Polymerase Chain Reaction (PCR) Typing kit. A total of 632 Dachshunds were sampled - 99 Standard Smooth-haired, 72 Standard Long-haired, 272 Standard Wire-haired, 42 Miniature Smooth-haired, 73 Miniature Long-haired and 74 Miniature Wire-haired. Average observed heterozygosity and polymorphic information content ranged in particular Da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
7
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 32 publications
5
7
0
Order By: Relevance
“…The mean number of alleles per locus was 6.43 (SD=1.47). Although a comparison with other breeds can be biased due to the different marker sets used by different authors, it may be noted that this value is near the upper range of the published values for other breeds: Greyhound, 2.5 alleles/locus; Labrador Retriever 3.3; German Shepherd, 3.3 (Zajc et al, 1997);Flat-coated Retriever, 4.5;Dachshund, 5.6 (Fredholm and Wintero, 1995); Andalusian Hound, 6.25; Spanish Greyhound 6.5; Maneto, 7.0 (Morera et al, 1997); Czech Dachshunds, 7.6 alleles/locus (Pribánová et al, 2009); and 12 East Asian dog breeds, 7.75 (Kim et al, 2001).…”
Section: Resultssupporting
confidence: 55%
“…The mean number of alleles per locus was 6.43 (SD=1.47). Although a comparison with other breeds can be biased due to the different marker sets used by different authors, it may be noted that this value is near the upper range of the published values for other breeds: Greyhound, 2.5 alleles/locus; Labrador Retriever 3.3; German Shepherd, 3.3 (Zajc et al, 1997);Flat-coated Retriever, 4.5;Dachshund, 5.6 (Fredholm and Wintero, 1995); Andalusian Hound, 6.25; Spanish Greyhound 6.5; Maneto, 7.0 (Morera et al, 1997); Czech Dachshunds, 7.6 alleles/locus (Pribánová et al, 2009); and 12 East Asian dog breeds, 7.75 (Kim et al, 2001).…”
Section: Resultssupporting
confidence: 55%
“…But, the average expected heterozygosity (He), polymorphic information content (PIC) and fixation index (F) calculated from the 16 microsatellite markers we analyzed were 0.665, 0.623 and 0.046, respectively. As the values were similar to research using different markers on Shiba Inus in Japan [ 8 ] as well as other popular breeds in other countries [ 3 , 10 , 15 , 17 ], it is suggested that the level of inbreeding in Shiba Inus is not so high as concerned.…”
supporting
confidence: 80%
“…We additionally examined a set of three breeds for which we collected samples in both the United States and Italy: Italian Greyhounds (Figure 1a), Cane Corsos (Figure 1v), and Neapolitan Mastiffs ( Figure 1w). As population substructure has previously been observed in international populations of breeds (Pedersen, Liu, Leonard, & Griffioen, 2015;Pedersen, Liu, McLaughlin, & Sacks, 2012;Quignon et al, 2007), we hope to characterize genetic divergence between US and Italian populations of Italian breeds, caused by importation bottlenecks, regional popular sire effects (Leroy & Baumung, 2010;Pribanova et al, 2009), or variation in selection. All three were correctly grouped by breed.…”
Section: Impact Of Geographic Separation On Breed Identity and Diffmentioning
confidence: 99%
“…Smaller studies exist which have addressed population demography in globally recognized breeds sampled from discrete locations with some success (Bigi, Marelli, Randi, & Polli, 2015;Ceh & Dovc, 2014;Koskinen & Bredbacka, 2000;Oliehoek, Bijma, & van der Meijden, 2009;Parra, Mendez, Canon, & Dunner, 2008;Pertoldi et al, 2013;Pribanova et al, 2009;Suarez, Betancor, Fregel, & Pestano, 2013;Wiener et al, 2017). While such studies provide insight into the status and genetic health of local populations, they do not necessarily consider the preexisting breedspecific genomic patterns developed prior to localization or the impact of import and export from the local breeding pool.…”
mentioning
confidence: 99%